What is religion? : a theological answer - Kumar, Nigel Ajay (Bangalore.; SAIACS Press., 2014)
"What is religion? is one of those questions rarely asked by Christian theologians who engage in interreligious discourse. Nigel Kumar makes the case, however, that to answer the question is critical for Christian scholars attempting to negotiate multiple religious identities, as well as for those who want a clearer understanding of their own faith as religion. Kumar takes a historical approach to answering the question. He traces the development of the concept of religion and then formulates a theological answer, not only by looking at an Indian theologian, Chenchiah, but also by listening to other secular and theological voices."
Keywords: Christian Theology; Chenchiah, P. 1886-1959; Religion; Theology of religions (Christian theology); Religion (discipline)